This preview shows page 1. Sign up to view the full content.
Unformatted text preview: R be R real numbers such that x r x s ( r = s ). Prove that R r =1  U ( x r )  2 2 K + 1 K k = K  b k  2 . (e) Let T ( x ) = M + N n = M +1 a n e ( xn ) . Prove that R r =1  T ( x r )  2 N + 1 M + N n = M +1  a n  2 Hint. Let K = N 2 , b k = a k + M +1+ K ( K k N K 1), b K = 0 when N is even....
View
Full
Document
This note was uploaded on 01/23/2012 for the course MATH 571 taught by Professor Vaughan,r during the Spring '08 term at Pennsylvania State University, University Park.
 Spring '08
 Vaughan,R
 Number Theory

Click to edit the document details